Nephroprotective Effects of Tetramethylpyrazine Nitrone TBN in Diabetic Kidney Disease - Jing, Mei; Cen, Yun; Gao, Fangfang; Wang, Ting; Jiang, Jinxin; Jian, Qianqian; Wu, Liangmiao; Guo, Baojian; Luo, Fangcheng; Zhang, Gaoxiao; Wang, Ying; Xu, Lipeng; et al. (Frontiers in Pharmacology, 2021)
Diabetic kidney disease (DKD) is the leading cause of end-stage renal failure, but therapeutic options for nephroprotection are limited. Oxidative stress plays a key role in the pathogenesis of DKD. Our previous studies demonstrated that tetramethylpyrazine nitrone (TBN), a novel nitrone derivative of tetramethylpyrazine with potent free radical-scavenging activity, exerted multifunctional neuroprotection in neurological diseases. However, the effect of TBN on DKD and its underlying mechanisms of action are not yet clear. Herein, we performed streptozotocin-induced rat models of DKD and found that TBN administrated orally twice daily for 6 weeks significantly lowered urinary albumin, N-acetyl-β-D-glycosaminidase, cystatin C, malonaldehyde, and 8-hydroxy-2′-deoxyguanosine levels. TBN also ameliorated renal histopathological changes. More importantly, in a nonhuman primate model of spontaneous stage III DKD, TBN increased the estimated glomerular filtration rate, decreased serum 3-nitrotyrosine, malonaldehyde and 8-hydroxy-2′-deoxyguanosine levels, and improved metabolic abnormalities. In HK-2 cells, TBN increased glycolytic and mitochondrial functions. The protective mechanism of TBN might involve the activation of AMPK/PGC-1α-mediated downstream signaling pathways, thereby improving mitochondrial function and reducing oxidative stress in the kidneys of DKD rodent models. These results support the clinical development of TBN for the treatment of DKD.